1980
DOI: 10.1073/pnas.77.9.5292
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an origin of DNA replication of Xenopus laevis.

Abstract: ABSTRACr DNA fragments of Xenopus laevis, the African frog, were cloned in the EcoRI site of the Escherichia coli Rlasmid pACYC189 and tested for ability to initiate and complete replication of the recombinant plasmid when injected into unfertilized eggs of X. laevis. After measurement of the [3HJ thymidine incorporation per egg for a number of recombinant plasmids, pSW14 and pSW9, which respectively contain a small segment (5SO base pairs) and several kilobases of frog DNA, were selected for more extensive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There have been several reports on the replication of foreign DNA injected into unfertilized eggs of X. laevis (7)(8)(9)(10)(11)(12). Recently, Harland and Laskey (12) to unlabeled RNA from injected embryos, treated with S1 nuclease, denatured, fractionated by gel electrophoresis, and autoradiographed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports on the replication of foreign DNA injected into unfertilized eggs of X. laevis (7)(8)(9)(10)(11)(12). Recently, Harland and Laskey (12) to unlabeled RNA from injected embryos, treated with S1 nuclease, denatured, fractionated by gel electrophoresis, and autoradiographed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, microneedle injection of DNA into Xenopus oocytes has provided a functional test to analyze the biological activity of cloned genes (2-5), a concept named "surrogate genetics" (6). Unfertilized eggs and egg extracts are reported to promote replication of injected DNA (7)(8)(9)(10)(11)(12). Fertilized eggs injected with DNAs (13, 14) or rabbit globin mRNAs (15) are able to continue developing into apparently normal tadpoles.…”
mentioning
confidence: 99%
“…Templates that replicate include bacteriophages X, M13, G4 and 4>X174, plasmids Col E l, pBR322, pMB9 and pAT153, together with a wide range of eukaryotic DNA fragments cloned into these vectors (Harland & Laskey 1980;McTiernan & Stambrook 1980;Mechali et al 1983;Mechali & Kearsey 1984). In contrast, there have been claims of sequence-specific initiation of replication in Xenopus eggs (Watanabe & Taylor 1980;Chambers et al 1982;Hines & Benbow 1982). A careful attempt to repeat these experiments (Mechali & Kearsey 1984) contradicted the claims of specific initiation and showed that replication is independent of DNA sequence, but depends on the size of the template DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators have tried to isolate replication origins by using in vitro recombination techniques (1, 16,21,41). Another approach to isolation of the replication origin is to get autonomous replicating sequences (ARS).…”
mentioning
confidence: 99%